A novel HNF1B mutation p.R177Q in autosomal dominant tubulointerstitial kidney disease and maturity-onset diabetes of the young type 5: A pedigree-based case report. Issue 31 (31st July 2020) - Tao, Tian; Yang, Yuan; Hu, Zhangxue
Abstract: Rationale: Mutations in the hepatocyte nuclear factor-1-beta ( HNF1B ) gene result in a very variable presentation, including maturity onset diabetes of the young (MODY), renal cysts, renal dysplasia, and autosomal dominant tubulointerstitial kidney disease (ADTKD), which is characterized by tubular damage, renal fibrosis, and progressive renal dysfunction. Patient concerns: A 22-year-old man came to the hospital presenting with hyperglycemia, hyperuricemia and elevated serum creatinine. His urine protein was within the normal range. The ultrasound examination revealed shrunken kidneys with renal cysts. The patient's mother was diagnosed with diabetes mellitus when she was 25 years old. Her laboratory results showed elevated serum creatinine. Her ultrasonography revealed shrunken kidneys with renal cysts and hydronephrosis without kidney stones. The next-generation sequencing revealed that the proband and his mother held the same heterozygous missense mutation (c.530G>A, NM_000458, p.R177Q) in the HNF1B gene. Bioinformatic analyses predicted that the mutation was likely pathogenic. Diagnosis: The patient and his mother were diagnosed as ADTKD and MODY5 due to HNF1B mutation. Intervention: The proband was administered metformin at a dose of 500 mg/day. Outcomes: The patient had well-controlled blood glucose levels and a stable renal function at his 12-month follow-up. Lessons: We should take into account the diagnoses of ADTKD and MODY5 if patients present with early onset diabetes and multiple renal cysts or evidence of renal tubulointerstitial dysplasia, especially those with negative proteinuria results. Genetic testing helps detect the HNF1B gene mutations.